Method of analysis of hierarchies as method of configuration of difficult systems - Задоров, В’ячеслав Борисович; Васильєв, Олександр Олександрович (Eastern-European Journal of Enterprise Technologies, 2014)
The author’s analysis of existing configurators as a set of programs that allow to structure and organize complex IT for certain domains with the implementation of functional tasks with a specified purpose and adaptation to particular standard situations is conducted. The author’s conceptual schematic diagram of the configurator and approach to creating the configurator considering the option for upgrading components are proposed. The authors have offered to use a mathematical hierarchy analysis method as a tool for forming a list of configurations and their features that the best satisfy the user. The method has been adapted to the peculiarities of the domain. Searching for the composite configuration, i.e. the package (portfolio) of software components as components of the optimal library of the system that performs and supports the efficient configured model of the program complex, i.e. the configuring system is carried out. From a mathematical point of view, the set of alternatives, i.e. configurations, optimal for the user, is defined as the Pareto set. The global weights of alternatives are found using the methods of distributive, ideal and multiplicative syntheses, supported by configurator. Using the hierarchy analysis method, which allows to select the optimal configurations for the user’s needs, the configurator-based complex systems are much more efficient than the monolithic systems with constant software package. Using the configurator, the user gets the software package, the most favorable in terms of business efficiency. The obtained results are used in developing the experimental configurator of information technologies in building (CIT-B) – Configurator of IT – the Patterns-maker of Building (C-IT PMB), which is aimed at configuring IT at certain stages of the life cycle of creating the building object.